Estudio de factibilidad para la creación de una empresa de eventos sociales en la ciudad de Pereira - Risaralda (2015)
The following project aims to develop the necessary studies that lead to the creation of a company specialized in providing a service specialized in the Organization of events, is aimed at the people of four levels and five believed to have greater purchasing power in the city of Pereira. Inside this report all the information that has been collected is registered and processed phases corresponding to the study of market, technical - operational, administrative, financial and economic, that ultimately will allow to establish the feasibility of creating enterprise in the city of Pereira, Risaralda, to provide an organized manner the events that demand persons. Research is carried out through fieldwork that establish trends for decisions, in addition to make use of all the tools as texts, brochures, reports, books, statistics, written documents of research undertaken in this regard, among others, that could contribute to the proper conduct of the investigation. In the project is managed to demonstrate the acceptability of a company with these features in the city of Pereira - Risaralda, which financially through the financial evaluation is viable to bring it to reality, since he threw a few positive return over investment which must incur to put in operation the company, therefore finally recommended the investment.